THE ROLE OF AGROFORESTRY APPROACH AS A POTENTIAL TOOL FOR ATTAINING CLIMATE SMART AGRICULTURE FRAMEWORK: BANGLADESH PERSPECTIVES - Talucder M.S.A.; Ruba U.B. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
The contribution of agroforestry methods in Bangladesh is examined in this review study as a climate-smart agriculture tool, including the aspects of i) Agroforestry as Food Security Capacity and Livelihood Improvement, ii) Sustainable land use through agroforestry for promoting resilience to climate change iii) Agroforestry and Mitigation of Greenhouse Gas Emission. The systematic review was conducted following the framework of PRISMA. The keywords "Agroforestry in Bangladesh", "Agroforestry and Food Security", "Agroforestry and Sustainability", and "climate-smart agriculture practices", “Agroforestry and Climatic Resilience” in the aspect of Bangladesh were entered into databases of PubMed and Scopus. Fifty-two original research articles were selected for systematic review. Agroforestry in Bangladesh produces food, firewood, fodder, and societal flexibility, sustaining output and enhancing livelihoods through revenue opportunity, according to the systematic review. Agroforestry systems boost productivity in several Bangladeshi locations, helping locals meet their food demands and earn more. It promotes carbon sequestration, sustainable land use, and greenhouse gas emission reduction. Many Bangladeshi agroforestry methods benefit the environment, people, and economy but institutional impediments prevent their use. However, the synthesis of Bangladeshi agroforestry literature helps determine how well agroforestry works and its future route and research aims, as it could help achieve sustainable development goals through it’s climate-smart trait.